The Evaluation of Using E-Learning as a Media of Japanese Language Listening Material for Beginner Learners - Yulianti, Vera (Universitas Negeri Jakarta, 2016)
This study is aimed to evaluate the effectiveness of using E-learning as a media of basicJapanese language listening material. The respondents are Basic Learners A2 level basedon CEFR and JFS. News from NHK Radio and video clips from NHK TV were designedas the listening materials to exercise the ability of predicting listening material contents.The respondents were asked to do the tasks inside university e-learning website. The resultshows that using E-learning as a media of listening material for basic language learners iseffective in condition of audio-visual task instead of audio task.